Trends in Indigenous and non‐Indigenous caesarean section births in the Northern Territory of Australia, 1986–2012: a total population‐based study. (18th January 2016) - Thompson, F; Dempsey, K; Mishra, G
Abstract : Objective: To examine trends in caesarean section deliveries and factors associated with these trends for Indigenous and non‐Indigenous mothers. Design: Total population‐based study. Setting: Northern Territory of Australia, 1986–2012. Population: Pregnancies among Northern Territory residents, limited to singleton live births with cephalic presentations delivered at 37–42 weeks' gestation ( n  = 78 561). Methods: Descriptive analyses of demographic and obstetric risk factors. Poisson regression with robust variance to estimate the likelihood of caesarean delivery with and without labour compared with vaginal delivery, over time and between Indigenous and non‐Indigenous mothers, adjusting for risk factors. Main outcome measures: Trends in caesarean sections and risk of caesarean delivery compared with vaginal delivery. Results: The total rate of caesarean deliveries in the Northern Territory increased between 1986 and 2012. From the year 2000, the rise was driven by increases in caesareans with labour among nulliparous mothers and no labour caesareans among multiparous mothers. Increases in demographic and obstetric risk factors explained the rise in caesareans with labour among nulliparous Indigenous mothers, whereas other unmeasured variables contributed to the rise among non‐Indigenous mothers. Increases in previous caesarean delivery contributed to the rise in all caesareans among multiparous mothers. Following adjustment, the risk of Indigenous nulliparous mothers having a caesarean with labour was 47% greater than for non‐Indigenous nulliparous mothers [adjusted risk ratio 1.47 (95% CI 1.34–1.60)]. Conclusions: Increases in demographic and obstetric risk factors partially explained the increase in caesarean rates in the Northern Territory and the contribution of these factors differed between Indigenous and non‐Indigenous mothers. Tweetable abstract: Caesarean section rates increased between 1986 and 2012 in the Northern Territory of Australia. Tweetable abstract: Caesarean section rates increased between 1986 and 2012 in the Northern Territory of Australia.